2013
DOI: 10.1155/2013/820956
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Executive Function and Obesity in Children and Adolescents: A Systematic Literature Review

Abstract: The objective of this paper is to examine the relationship between the development of executive function (EF) and obesity in children and adolescents. We reviewed 1,065 unique abstracts: 31 from PubMed, 87 from Google Scholar, 16 from Science Direct, and 931 from PsycINFO. Of those abstracts, 28 met inclusion criteria and were reviewed. From the articles reviewed, an additional 3 articles were added from article references (N = 31). Twenty-three studies pertained to EF (2 also studied the prefrontal and orbito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
206
3
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(234 citation statements)
references
References 59 publications
(66 reference statements)
18
206
3
7
Order By: Relevance
“…The study by Jastreboff et al (9) describes functional differences in the central nervous system during response to fructose or glucose solutions. First, the executive center in the prefrontal cortex is inhibited in the obese, confirming earlier work in adolescents (11,12) and adults where Volkow et al (13) showed a significant negative correlation between BMI and metabolic activity in prefrontal cortex and cingulate gyrus. Using leptin as a surrogate for fatness, Jastreboff et al (9) found that it was inversely related to blood flow in the prefrontal cortex.…”
supporting
confidence: 83%
“…The study by Jastreboff et al (9) describes functional differences in the central nervous system during response to fructose or glucose solutions. First, the executive center in the prefrontal cortex is inhibited in the obese, confirming earlier work in adolescents (11,12) and adults where Volkow et al (13) showed a significant negative correlation between BMI and metabolic activity in prefrontal cortex and cingulate gyrus. Using leptin as a surrogate for fatness, Jastreboff et al (9) found that it was inversely related to blood flow in the prefrontal cortex.…”
supporting
confidence: 83%
“…In a developmental perspective, young children's decisions are based primarily on short-term outcomes [4], and this tendency decreases throughout childhood until late adolescence [5]. A key structure involved in decision-making under uncertainty (i.e., with unknown outcomes) is the orbitofrontal cortex (OFC) [6], a region that shows specific structural and functional variations in overweight/obese as compared to normal-weight children and adults [e.g., [7,8]]. Moreover, a reduced OFC volume has been associated with (un)healthy food choices [9], so a potential association between decision-making deficits and overweight might be mediated by this brain region.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, obese and overweight children and adolescents show inferior executive functioning than do their normal-weight peers [7]. However, only few studies with children and adolescents have investigated weight-group differences in decision-making under uncertainty, as measured with the IGT, so it is unclear at which age the weight-group differences develop.…”
Section: Introductionmentioning
confidence: 99%
“…In prospektiven Studien zeigte sich eine geringe inhibitorische Kontrolle als prädiktiver Faktor für einen mehrere Jahre später höheren BMI [vgl. Reinert et al, 2013], aber auch als prädiktiver Faktor für geringeren Gewichtsverlust nach einem Gewichtsreduktionsprogramm [Nederkoorn et al, 2007]. Innerhalb der Gruppe von Kindern und Jugendlichen mit Adipositas lassen sich weiterhin Subgruppen differenzieren.…”
Section: Chronobiologie Persönlichkeitseigenschaften Und Neurokognitunclassified
“…Neben einer geringeren inhibitorischen Kontrolle finden sich bei adipösen Kindern und Jugendlichen ebenfalls Defizite in anderen exekutiven Funktionen wie beispielsweise der Arbeitsgedächtnisleistung oder bei Aufgaben, die mentale Flexibilität erfordern [Reinert et al, 2013]. Diese Zusammenhänge scheinen spezifisch die exekutiven Funktionen zu betreffen, da sie auch nach Einbezug allgemeiner kognitiver Funktionen der Betroffenen (z.B.…”
Section: Chronobiologie Persönlichkeitseigenschaften Und Neurokognitunclassified